Quality management in oil and gas turnaround/shutdown projects / Ghadaffi Rosli - Ghadaffi, Rosli (2020)
This study discusses the problem of defining quality in the oil and gas industry, to determine possible benefits of implementing quality, and to identify barriers of quality implementation in the oil and gas industry. Quality management is the process for ensuring that all project activities necessary to design, plan and implement a project are effective and efficient with respect to the purpose of the objective and its performance. Specifically in the oil and gas Turnaround Maintenance / Shut down Maintenance project, a comprehensive understanding of issues related to project quality is required. This research aims to investigate the benefit and barrier of quality management in the oil and gas industry. The main objective of this research is to determine the importance of quality management implementation in oil and gas TAM/SM projects. This research also aims to highlight the benefits of implementing the quality management to the overall project delivery. In addition, recommendations to improve the quality management implementation in Malaysiaï¿½s oil and gas industry will be made. Data for this research was conducted by sending questionnaire survey to the oil and gas industry players. From the data collected, it has been found that the client satisfaction, education, and training are the most important measure to improve quality performance. The findings show that certified quality programmes such as the ISO 9000 series are important. Keywords: quality management; oil and gas; industry.